The Improving Students’ Mathematics Results and Interest Through Online-Based Flipped Classroom Models - Hamidah, H; Kusuma, Jaka Wijaya (Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
People know that the internet today has become an integral part of the lifestyle of various Indonesian community groups, but the results of surveys conducted by the Indonesian Internet Network Organizing Association are known to have access to educational pages are still very lacking. The online-based flipped classroom learning model is packaged to appeal to students and is a learning that adapts online learning in times of pandemic by directing students to utilize the internet for learning. This study was a classroom action research by applying online-based flipped classroom model to improve Students’ Mathematics Result And Interest. The classroom action research was done in two cycles. Each cycle consists of planning, action, observation, and reflection. The findings of this research revealed that the online-based flipped classroom model could improve students’ mathematics results and interest. At the end of the first cycle, the students’ mathematics result was still in the medium category and increased at the end of the second cycle, which students’ mathematics result has been in high category, and students’ mathematics interest has been more than 80% that is reaching the expected target.